2003
DOI: 10.1016/s0045-6535(02)00598-2
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cu and Pb by tartaric acid modified rice husk from aqueous solutions

Abstract: A study on the modification of rice husk by various carboxylic acids showed that tartaric acid modified rice husk (TARH) had the highest binding capacities for Cu and Pb. The carboxyl groups on the surface of the modified rice husk were primarily responsible for the sorption of metal ions. A series of batch experiments using TARH as the sorbent for the removal of Cu and Pb showed that the sorption process was pH dependent, rapid and exothermic. The sorption process conformed to the Langmuir isotherm with maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
185
0
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(211 citation statements)
references
References 11 publications
16
185
0
10
Order By: Relevance
“…The pseudo-second-order kinetic analysis reveals that the value of the initial adsorption rates (h) increases with increase in the initial Pb 2+ ion concentration. The lower the concentration of metal ions in the solution, the lower the probability of collisions between these species and, hence, the faster Pb 2+ ions can bond to the active sites on the surface of the adsorbent (Wong et al, 2003). Figure 7: Pseudo-second-order plot for Pb 2+ ion adsorption onto NSSCAC at different concentrations.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pseudo-second-order kinetic analysis reveals that the value of the initial adsorption rates (h) increases with increase in the initial Pb 2+ ion concentration. The lower the concentration of metal ions in the solution, the lower the probability of collisions between these species and, hence, the faster Pb 2+ ions can bond to the active sites on the surface of the adsorbent (Wong et al, 2003). Figure 7: Pseudo-second-order plot for Pb 2+ ion adsorption onto NSSCAC at different concentrations.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…The presence of lead in drinking water even at low concentration may cause diseases such as anemia, encephalopathy, hepatitis and nephritic syndrome (Lo et al, 1999). Lead is non-biodegradable and can accumulate in living tissues, thus becoming concentrated throughout the food chain, and can be readily absorbed into the human body (Wong et al, 2003). Even a very small amount can cause severe physiological or neurological damage to the human body.…”
Section: Introductionmentioning
confidence: 99%
“…at mildly elevated temperatures enhance their sorption capacity for metal ions and basic dyes (Lehrfeld 1997;Wafwoyo et al 1999;Marshall et al 1999Marshall et al , 2000Vaughan et al 2001;Wong et al 2003;Altundogan et al 2007;Gong et al 2006Gong et al , 2007Gong et al , 2008. It has been reported that an estimated production cost for citric acid-modified soybean hull is $1.17/kg versus typical retail costs $4-40/kg for commercial, petroleum-based cation exchange resins when purchased in bulk quantities .…”
Section: Introductionmentioning
confidence: 99%
“…where the K (mg g-1) and n (value between 0 and 1) are the Freundlich constant characteristic on the system. K and n are indicators for adsorption capacity and adsorption intensity, respectively [14][15][16][17][18][19][20][21][22].…”
Section: Equilibrium Studiesmentioning
confidence: 99%